Digital transformation framework - Tarhini, Abbas (2018)
Today, with increased global awareness to protect natural resources and secure private assets, digital transformation is becoming an obligation in large public enterprises such as modern utility firms and armed forces that overlaps massive resources while executing business processes. In such firms, different forces are driving the business environment aiming at satisfying the public needs, controlling expenses, and maximizing the use of available assets. Thus, a balance should be made between the service flow to the public and the financial flow back to the firm. In this regard, digital transformation is essential to monitor, identify, control and track the profit or loss of operations in different firm units. Traditionally, firms’ management used to be supported by Automation and Information Technology; but such a support was limited to isolated applications form several vendors in different departmental units, with a major drawback such as overlapping functions, and lack of coordination and standardization that lead to several organizational failures. The digital transformation in modern firms requires a framework that facilitates the development of a digital vision and optimizes business models that integrate operational activities, apply economic analysis, target public needs, perform managerial tasks, and support decision making. Despite the ongoing development in industry relevant to this topic, there exists modest research attempts in academia, and there is a gap in research on digital transformation frameworks. In this paper, various digital transformation cases studies from different utility firms operating in the Gulf region are explored; further, the needed platform and a framework to develop digital transformation blueprint is presented together with a digital transformation roadmap.